In silico characterization of Cnidarian’s antimicrobial peptides - Leal, Edwar; Múnera, Marlon; Suescún-Bolívar, Luis Parmenio (Frontiers in Marine Science, 2022)
The characterization of active compounds in Cnidaria sheds light on a large bank of substances against multiresistant bacteria related to diseases in humans, which makes it a cutting edge with a repertoire of antimicrobial molecules worthy of bioprospecting analysis. Thus, the main nabof this research was to characterize antimicrobial peptides (AMP) belonging to the defensin family in different species of Cnidarians through bioinformatic approaches. To this, an exhaustive search was carried out for sequences homologous to antimicrobial peptides belonging to the defensin family in genomes availables for Cnidarians. Also, 3D models of AMP were obtained by modeling based on homology, functional characterization of peptides found was performed with machine learning approaches. Characterization of twelve peptides derived from 11 Cnidarian species was possible due to 3D modeling, which showed structural similarity with defensins reported in several species such as Nasonia vitripennis, Pisum sativum, Solanum lycopersicum, and Aurelia aurita. Also, different physicochemical properties such as hydrophobic moment, hydrophobicity, net charge, amphiphilic index, and isoelectric point were evaluated. These peptides showed values ​​that are ideal for AMP. Further, functional characterization showed a bactericidal potential of 20 peptides against multiresistant bacteria Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae. These peptides with action potential were found in 17 species from Cnidarians and obtained by homology through the defensin Aurelin, described in the Cnidarian Aurelia aurita, and Mus musculus’ Beta-defensin 7. Finally, a phylogenetic tree was performed, it showed that defensins are distributed in all Cnidarians regardless of the taxonomic group. Thus, the origin of defensins in the Phylum Cnidaria is not monophyletic. Our results show that Cnidaria has AMP with structural and physicochemical characteristics similar to those described in defensins of insects, mammals, and plants. The structural characteristics of these peptides, their physicochemical properties, and their functional potential outline them as promising templates for the discovery of new antibiotics.